Bioremediation of Oil Spill using Dried Coconut Husk as an Absorbent Material - Tamaratritania Citta Trisnantari; Gede Wiratma Jaya; Nikmans Hattu (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
Oil spills represent a serious environmental hazard, particularly to marine ecosystems. This study explores the use of dry coconut husk, an abundant agricultural waste, as a natural sorbent for oil spill remediation. The oil absorption performance of coarse and powdered coconut husk was evaluated under various conditions, including different contact times, absorbent masses, and oil–water mixtures. A commercial oil absorbent pad (SABER) was used as a benchmark. Results show that powdered coconut husk has higher absorption capacity and efficiency compared to coarse husk, attributed to its finer particle size and increased surface area. In oil–water systems, powdered husk exhibited selective oil uptake with minimal water absorption, approaching the performance of the commercial pad. These findings highlight the potential of coconut husk as a biodegradable, low-cost, and sustainable sorbent material, especially in resource-limited settings. Its direct use without chemical modification supports practical applications and aligns with circular economy principles. Further optimization and field-scale validation are recommended to enhance its applicability in real spill scenarios.